2016
DOI: 10.2151/sola.2016-037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of GOSAT Observations on Estimates of Net CO<sub>2</sub> Flux in Semi-Arid Regions of the Southern Hemisphere

Abstract: Greenhouse gases Observing SATellite (GOSAT) is the operational satellite dedicated to atmospheric CO 2 observations. Assimilation of data provided by GOSAT is expected to yield reliable CO 2 fluxes in semi-arid regions because of frequent observations owing to clear skies. Here we estimated net CO 2 flux over semi-arid regions of the Southern Hemisphere using the GOSAT column averaged CO 2 (X CO2 ) and surface CO 2 measurements. Assimilation of GOSAT X CO2 indicated that semi-arid regions are integral compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…to the carbon sink due to human mitigation efforts or responses of the biosphere to prior events?). (NBP) from the natural biosphere (Buchwitz et al, 2017;Kondo et al, 2016).…”
Section: Le Sson 6 -Advan Ce S Made Via Synerg Ie S With Remote S Ens...mentioning
confidence: 99%
See 1 more Smart Citation
“…to the carbon sink due to human mitigation efforts or responses of the biosphere to prior events?). (NBP) from the natural biosphere (Buchwitz et al, 2017;Kondo et al, 2016).…”
Section: Le Sson 6 -Advan Ce S Made Via Synerg Ie S With Remote S Ens...mentioning
confidence: 99%
“…They analysed the hydroclimate drivers and pulse response behaviour of carbon fluxes during the big wet and reported that semi‐arid Australian net CO 2 uptake was highly transient and rapidly dissipated by subsequent drought. The accuracies of the remotely sensed CO 2 retrievals and the atmospheric transport models are approaching the levels needed to constrain CO 2 fluxes to estimate net biome productivity (NBP) from the natural biosphere (Buchwitz et al, 2017; Kondo et al, 2016).…”
Section: Lesson 6—advances Made Via Synergies With Remote Sensingmentioning
confidence: 99%